Dependência de exercício físico: humor, qualidade de vida em atletas amadores e profissionais - Modolo, V. B.; Mello, M. T. de; Borba de Gimenez, P. R.; Tufik, S.; Antunes, H. K. M. (Revista Brasileira de Medicina do Esporte, 2009)
The purpose of this study was to verify if there are differences between exercise dependence (ED), mood and quality of life scores in professional and amateur athletes of individual and collective sport modalities. METHODS: 116 male athletes of collective sport modalities (n=60, 20 professionals and 40 amateurs) and individual sport modalities (n=56, 16 professionals and 40 amateurs) participated in this study. Age, height, weight, BMI mean (± standard-deviation) were: 22.13 ± 6.16 years; 1.77 ± 0.10 cm; 72.76 ± 10.04 kg and 23.10 ± 2.04 kg/m2, respectively. The athletes answered the following questionnaires: Exercise Dependence scale (EDE), Beck Depression Inventory, Trait and State of Anxiety - IDATE, POMS - profile of mood states, SF-36 Questionnaire of Quality of Life. The study was approved by the Ethics in Research Committee of UNIFESP (0616/06). RESULTS: Amateur and professional athletes presented similar scores of ED, but when the kind of modality was considered, the amateurs of collective modalities presented higher scores than professional athletes. CONCLUSION: Amateur and professional athletes of collective and individual sport modalities answered differently to ED, and the sports modality and competitive and social involvement could be determinant. Moreover, it is possible to conclude that professional athletes of collective sports present better profile of mood and quality of life when compared with professional athletes of individual sports when compared with amateur athletes from collective or individual sport modalities.